2023
DOI: 10.1111/chso.12678
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identity in school context: The case of Yi ethnic minority adolescents in rural China

Abstract: Using Yi adolescents in rural China (n = 163) as an example, this qualitative study explored how school ethnic socialization shaped the ethnic identity development and the future self of indigenous youths in mainstream Han‐dominant school settings. Focus groups and thematic analysis were used. Six themes emerged, describing the participants' experiences of mainstream socialization, cultural socialization and multiculturalism within their school and how these practices shape their ethnic identity. Mainstream so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Interestingly, earlier findings on younger Yi youths indicated a decline in their ethnic identity exploration and commitment [45]. This discrepancy may be explained by the distinct developmental stages of childhood versus adolescence: at earlier developmental stages, Yi young people may not be aware of their ethnic distinctiveness [7].…”
Section: Key Finding 1: Ethnic Identity Development In Yi Adolescentsmentioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, earlier findings on younger Yi youths indicated a decline in their ethnic identity exploration and commitment [45]. This discrepancy may be explained by the distinct developmental stages of childhood versus adolescence: at earlier developmental stages, Yi young people may not be aware of their ethnic distinctiveness [7].…”
Section: Key Finding 1: Ethnic Identity Development In Yi Adolescentsmentioning
confidence: 82%
“…Findings on Yi primary-school children showed that they developed positive social skills, behavioral health, and academic motivation after attending the local schools [34,44]. However, these students' sense of ethnic identity declined over time [45]. The rural education curriculum focuses on academic excellence and preparing students to survive in the Han-driven economy, resulting in school management placing a lower priority on the teachings of ethnic minority culture and traditions [46][47][48].…”
Section: Context Of This Research: the Case Of The Yi Ethnic Minority...mentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive ethnic-racial socialization in school settings is a proven source of strong ethnic identity and positive psychological health in ethnic-racial minority young people in Western literature (e.g., Byrd, 2019 ; Saleem and Byrd, 2021 ). Research conducted by the authors of this article among Asian students also showed that through learning about and discussing their own cultures in relation to larger society and issues on racial equality and justice at their schools, which is, an immediate social context that young people are nested in, students are given the opportunity to resolve ethnic uncertainties and leverage their ethnicity to develop their sense of life purpose (e.g., Lai et al, 2023 ; Teyra et al, 2023 ). While scholars have been focusing on the study of ethnic identity in ethnic-minority young people, there is also a growing discussion on the importance of ethnic identity for the cultural majority.…”
Section: Introductionmentioning
confidence: 95%
“…Some showed pride and positive feelings towards their ethnic group membership, while others preferred to disengaged from their ethnic communities because of racial discrimination. On the other hand, some students were able to resolve their racial discrimination experiences and pledged to contribute to their ethnic community with the mainstream knowledge they learned at school ( Lai et al, 2023 ). These findings suggested that ethnicity do play a special role within the development of ethnic minority individuals in different socio-cultural settings.…”
Section: Introductionmentioning
confidence: 99%